(3cJGH aj Yde GdUQas ((3MGaX edG UGdM s)
(3ChdgG (B:s
(3EYde Cf GdJUQja ai GddZI GdJZjjQ hai GdUfGYI JMhjd GdCUd GdhGMO Edi CeKdI eNJdaI deYGf ebUhOI dG JMUd EdG HgG s
(3BNQgG (B:s
(3hGdaYdi HGdcSQ ddfhY ef GdaYd , hgh MSf jWYeI hGdLdSI Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf hGdahGJM HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas